Assistance with a Zero Waste-Based Integrated Farming System to Address Waste Problems and Support Food Security in the Dharmasraya Fish Farming Group - Purnomo, Wulan Andang; Ferdinal, Alex; Sari, Mistia; Efendi, Raimon (Unpad Press, 2025)
Dharmasraya Regency has great potential in the freshwater fisheries sector but still faces challenges in waste management and business efficiency. This community service program aims to enhance the productivity and sustainability of fish farming through the application of a Zero Waste-based Integrated Farming System. Activities were carried out through a participatory approach involving socialization, training, and mentoring for the Rangkiang Farm Fish Farmers Group. The proposed solutions include processing organic waste into maggot feed, utilizing compost produced from maggot cultivation, and adopting Internet of Things (IoT) technology and digital marketing. The results show increased production efficiency, with up to 50% of fish feed sourced from organic waste, and improvements in managerial skills and digital marketing capabilities. Waste banks and recycling programs were also established, reflecting growing environmental awareness within the community. The findings conclude that the circular economy approach can be effectively implemented at the community level. Follow-up actions include model replication, institutional strengthening, and collaboration with local government and the private sector to ensure program sustainability.